MENGHITUNG DETERMINAN MATRIKS DENGAN MENGGUNAKAN METODE SALIHU - Andi Bahota; Aziskhan Amri; Musraini M. (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
This article presents a new method to calculate order determinants. This article is a review of Salihu’s papers [Internationational Journal of Algebra, 6(19): 913917, 2012]. Some examples are presentedat the end of discussion.